Functional dimorphism and relationship between different lower extremity strength tests in young elite judokas - Kursat Acar (Universidad de León, 2021)
The present study investigated the limb symmetry index (LSI) and the relationship between different functional strength tests in young elite judokas. Seventeen males (age= 16.88±1.40 years, height= 179.00±7.00 cm, weight= 78.76±15.22 kg and BMI 24.40±3.36 kg/m2) participated in the study voluntarily. Participants were tested with single leg (SL), and triple leg (THD) hop for distance, crossover hop for distance (CHD), 6 m Timed Hop Test (6mTHT), and single-leg vertical jump (SLVJ) tests, and countermovement jump (CMJ). All SL hop tests (SLHT) were applied to both right (Rs) and left sides (Ls), while CMJ was applied as without (CMJWAS) and with arm swing (CMJAS). Paired sample t-test and Pearson correlation tests were used in statistical analyses. In all SLHTs, no statistical significance was found between Rs and Ls. However, significance was found between CMJWAS and CMJAS. There was also no significance in LSIs between all SLHTs. Correlations were found between SL, THD, CHD, VJ tests, while negative and significant correlations were found between SL, THD, CHD, VJ tests, and 6 m THT. No significance was found between SLHTs and CMJWAS and CMJAS. As a result, it was found that Rs and Ls of young judokas produced similar strength in SLHTs, while they caused differences in CMJWAS and CMJAS values; when evaluated in terms of LSI, judokas showed similar rates in all SLHTs, and these rates were within reliable ranges; SLHTs had correlations with each other, but they did not show any correlation with CMJ.